FRI0311 Coevolution of a URIC Acid Transporter and Uricase: Implications for Gout. (9th June 2015) - Tan, P.K.; Gaucher, E.A.; Miner, J.N.
Abstract : Background: Gout is caused by chronic hyperuricemia, leading to uric acid deposition. Humans and apes have relatively high serum uric acid (sUA) levels due to inactivating mutations in the enzyme uricase which took place during hominid evolution, preventing the conversion of uric acid into more soluble allantoin. Uric acid is eliminated primarily by excretion through the kidneys. Most gout patients exhibit reduced renal excretion of uric acid. In the kidney, most of the uric acid is reabsorbed back into the bloodstream through URAT1, a uric acid transporter that is essential for maintaining sUA levels. From our studies on URAT inhibitors, we identified phenylalanine 365 as important for inhibitor affinity. We now find that this residue also affects the affinity of URAT1 for the substrate uric acid. Evolutionary changes in this amino acid appear to track with alterations in uricase function. Objectives: To determine whether URAT1 may have been subject to adaptive evolution for controlling and maintaining the relatively high sUA levels in humans. Methods: Ancestral URAT1 sequences were inferred by analyzing modern transporter sequences within an evolutionary framework. Briefly, extant sequences were collected and used to infer a phylogenetic tree. Ancestral sequences were then computationally inferred from the tree and then synthesized and cloned in the laboratory. Modern and ancestral URAT1 genes were transiently expressed in HEK-293T cells to measure URAT1-dependent transport of uric acid. The affinity of each construct for uric acid was determined. Results: Among the URAT1 orthologs, residue 365 is phenylalanine in humans, apes, and monkeys, but is tyrosine in most other mammals. Ancestral sequence analysis reveals that the tyrosine to phenylalanine replacement occurred deep in the primate lineage. Human URAT1 has a significantly higher affinity for uric acid (Km ∼ 150 μM) compared to rat URAT1 (Km ∼ 800 μM). Point mutant chimeras between the two transporters show that human phenylalanine 365 confers a higher affinity to uric acid. The transport activities of ancestral and other modern orthologous URAT1 proteins also indicate that phenylalanine 365 is important for high uric acid affinity. Remarkably, the known decrease in primate uricase activity tracks concomitantly in evolutionary history with the alterations that increase uric acid affinity of URAT1 during primate evolution. Conclusions: Human URAT1 phenylalanine 365 is important for high affinity transport of uric acid, while URAT1 orthologs and ancestors that carry tyrosine 365 have low affinity transport of uric acid. Evolutionary analysis shows that the tyrosine-to-phenylalanine conversion in URAT1 coincides with the inactivating mutations in uricase that took place between 45-90 million years ago, suggesting that this URAT1 mutation occurred due to adaptive positive selection for elevated uric acid levels in humans and their closest relatives. We posit that phenylalanine 365, along with other residues, plays an important role in URAT1-dependent uric acid homeostasis. References: PK Tan, D Hyndman, and JN Miner. Lesinurad, an Inhibitor of the Uric Acid Transporter URAT1 and Potential Therapy for Gout, Requires URAT1 Phenylalanine 365 for High Affinity Inhibition. Ann Rheum Dis 2014:73(Suppl2). Acknowledgements: Editorial support for this abstract was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: P. Tan Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, E. Gaucher Grant/research support from: Dupont, J. Miner Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group